2006
DOI: 10.1620/tjem.209.207
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Impact of .BETA.-D Glucan on Invasive Fungal Infection for the Living Donor Liver Transplant Recipients

Abstract: infection is a fatal complication in liver transplantation and it is very difficult to diagnose at the early stage. The aim of this study was to review our experience with invasive fungal infections in living donor liver transplantation (LDLT) and to analyze the risk factors and the impact of β -D glucan. From 1991 to 2005, 96 LDLTs were performed in our institution and we measured the serum level of β -D glucan in order to clarify the diagnosis. Invasive fungal infection was diagnosed based on clinical sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
(38 reference statements)
1
23
0
Order By: Relevance
“…The commonly used surveillance cultures lack the necessary sensitivity to detect IFI on time for efficient treatment. Accordingly, the level of serum β-D-glucan, a fungal cell wall component, has been used for rapid diagnosis [39, 40], and has been confirmed as efficient diagnostic test for early diagnosis of IFI [16, 40, 41]. The results of the present study support the sensitivity and specificity of β-D-glucan reported in the above studies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The commonly used surveillance cultures lack the necessary sensitivity to detect IFI on time for efficient treatment. Accordingly, the level of serum β-D-glucan, a fungal cell wall component, has been used for rapid diagnosis [39, 40], and has been confirmed as efficient diagnostic test for early diagnosis of IFI [16, 40, 41]. The results of the present study support the sensitivity and specificity of β-D-glucan reported in the above studies.…”
Section: Discussionsupporting
confidence: 87%
“…The results of the present study support the sensitivity and specificity of β-D-glucan reported in the above studies. Interestingly, other groups used a different method for β-D-glucan measurement or used different cut-off values [16, 41]. Further studies are needed to determine the optimal cutoff value of serum β-D-glucan for LDLT patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was useful for the diagnosis of invasive aspergillosis in living-donor liver allograft recipients in one study (49). A pan fungal PCR in the blood was shown to be helpful and preceded clinical signs of invasive fungal infections in renal transplant recipients by 27 days (50 Since this study, a number of reports of employing voriconazole for the treatment of invasive aspergillosis in SOT recipients have appeared in the literature.…”
Section: Invasive Aspergillosis In Sot Recipientsmentioning
confidence: 85%
“…However, false-positive galactomannan tests have been documented in up to 13% of liver transplant recipients (Kwak et al, 2004), but the sensitivity of the assay for the diagnosis of invasive aspergillosis may be improved by testing bronchoalveolar lavage . The diagnosis of invasive aspergillosis using the 1-3, beta-d-glucan assay has not been fully defined, but one study has shown that the test was useful for the diagnosis of invasive aspergillosis in living-donor liver transplant recipients (Kawagishi et al, 2006). Currently, prophylaxis against invasive aspergillosis is not routinely recommended in all solid organ transplant recipients.…”
Section: Aspergillus Speciesmentioning
confidence: 99%